Physical profile differences between the players of the first two men's handball leagues in Romania - Trofin, P. F.; Honceriu, C.; Tanasa, A. R. (Bulletin of the Transilvania University of Brasov, Series IX: Sciences of Human Kinetics, 2022)
The purpose of this research is to create a physical profile of the handball player. The results of 133 handball players from the first two leagues of Romania were analyzed. The players in the first league are taller, heavier, but without significant differences from those in the second league in body fat or muscle mass. The developed explosive force (SJ, CMJ, and FJ) indicated close values. Spine mobility is superior to second league players. The maximum oxygen consumption is higher in the first league players (56.24±0.53 ml/kg/min). The results indicated the need for superior anthropometric characteristics for the first men`s handball league, but also physical characteristics that would give players a great capacity for effort.